2021
DOI: 10.3389/fphys.2021.716721
|View full text |Cite
|
Sign up to set email alerts
|

Communication Between Cardiomyocytes and Fibroblasts During Cardiac Ischemia/Reperfusion and Remodeling: Roles of TGF-β, CTGF, the Renin Angiotensin Axis, and Non-coding RNA Molecules

Abstract: Communication between cells is a foundational concept for understanding the physiology and pathology of biological systems. Paracrine/autocrine signaling, direct cell-to-cell interplay, and extracellular matrix interactions are three types of cell communication that regulate responses to different stimuli. In the heart, cardiomyocytes, fibroblasts, and endothelial cells interact to form the cardiac tissue. Under pathological conditions, such as myocardial infarction, humoral factors released by these cells may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 168 publications
0
13
0
Order By: Relevance
“…Moreover, we demonstrated that intracellular TAGE induces cell death in HCF. Based on the previous studies, we considered that death of HCF directly inhibited the role of them more than the suppression of HCF activation or differentiation [ 3 , 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, we demonstrated that intracellular TAGE induces cell death in HCF. Based on the previous studies, we considered that death of HCF directly inhibited the role of them more than the suppression of HCF activation or differentiation [ 3 , 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a lifestyle-related disease (LSRD) caused by the dysfunction and cell death of cardiomyocytes via ischemic or non-ischemic events [ 1 , 2 , 3 ]. Cardiac fibroblasts are crucial for the repair and remodeling of the heart.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations